A single‐nucleotide polymorphism in the human ENTPD1 gene encoding CD39 is associated with worsened graft‐versus‐host disease in a humanized mouse model. Issue 5 (16th April 2020) - Adhikary, Sam R; Cuthbertson, Peter; Turner, Ross J; Sluyter, Ronald; Watson, Debbie
Abstract: Regulatory T cells (Tregs) protect against graft‐ versus ‐host disease (GVHD), a life‐threatening complication of allogeneic hematopoietic stem cell transplantation. The ectoenzyme CD39 is important for increasing the immunosuppressive function of Tregs. The rs10748643 (A → G) single‐nucleotide polymorphism (SNP) in intron 1 of the human ENTPD1 gene is associated with increased proportions of CD39 + Tregs. This study aimed to determine whether the rs10748643 SNP corresponded to increased proportions of CD39 + Tregs in an Australian donor population, and whether this SNP influences clinical GVHD in a humanized mouse model. Donors were genotyped for the rs10748643 SNP by Sanger sequencing, and the proportion of CD39 + T cells in donor peripheral blood was determined by flow cytometry. Donors encoding the G allele (donors AG/GG ) demonstrated higher proportions of CD39 + CD3 + CD4 + CD25 + CD127 lo Tregs, but not CD39 + CD3 + CD8 + T cells or CD39 + CD3 + CD4 + conventional T cells, compared with donors homozygous for the A allele (donors AA ). NOD‐SCID‐IL2Rγ null mice were injected with human peripheral blood mononuclear cells from either donors AA (hCD39 AA mice) or donors AG/GG (hCD39 AG/GG mice). hCD39 AG/GG mice demonstrated significantly greater weight loss and GVHD clinical scores, and significantly reduced survival, compared with hCD39 AA mice. hCD39 AG/GG mice showed significantly higher hCD4 + :hCD8 + T‐cell ratios than hCD39 AA mice, but displayed similar proportions of CD3 + hCD4 + hCD25 + hCD127 lo Tregs and hCD39 + Tregs. However, the proportion of human Tregs corresponded to survival in hCD39 AA mice, but not in hCD39 AG/GG mice. This study demonstrates that donors encoding the G allele show higher percentages of CD39 + Tregs, but cause worsened GVHD in humanized mice compared with donors homozygous for the A allele. Abstract : The rs10748643 single‐nucleotide polymorphism (SNP; A → G) in the human ENTPD1 gene influences the suppressive capabilities of regulatory T cells (Tregs), which protect against graft‐ versus ‐host disease (GVHD). NOD‐SCID‐IL2Rγ null mice were injected with human peripheral blood mononuclear cells from either donors AA (hCD39 AA mice) or donors AG/GG (hCD39 AG/GG mice) for the ENTPD1 gene.This study demonstrates that donors encoding the G allele of the rs10748643 SNP show higher percentages of CD39 + Tregs, but cause worsened GVHD in humanized mice compared with donors homozygous for the A allele.